INDONESIA CBM DEVELOPMENT CHALLENGES AND OPPORTUNITIES - Susilawati, Siti Sumilah Rita; Hadiyanto, Hadiyanto (Buletin Sumber Daya Geologi, 2006)
The increasing price of oil in the world market andthe depleted national oil reserves while on the otherhand there is a high dependency on oil as nationalmain source of energy, promote the development ofnew energy alternative in Indonesia. Apart from oil,Indonesia is also known to have contained enormousresources of conventional gas, coal, hydropower andgeothermal. Furthermore due to its significant coalresources, coal bed methane becomes one of the newpromising alternative energy in Indonesia.